EDUCATION AND SCIENCE AS FACTORS OF INNOVATIVE ECONOMICS DEVELOPMENT - Galiyeva, A.Kh.; Sadu, Zh.N.; Kulubekov, M.T.; Kazbekova, L.A. (Academic Journal of Physical and Chemical Sciences, 2018)
This work is aimed at analysis of education and science role as a system of structure elements that form the innovative economics. The tasks are: reveal the notion of education and science, analyze its constituents and its role in operating process of innovative economics, and analyze its interconnection as structural system-forming elements. The following methods were used to implement the work: graphical analysis, methods of deduction and induction, and analysis of semantic sources. The research results showed some correlation between the education level and a degree of innovative development of economics; the features of social demand in the education field in view of market economics were revealed, and as result, the education goals in knowledge economy were determined. The results can be used for correction of the national policy in the field of education and science management. The authors have come to a conclusion that for successful forming of innovative economy it is necessary to transit from less flexible convey of practical knowledge to teaching the skills on knowledge application.